Chapter Interventions for non-self-sufficiency - Focus on care and social policies in South Tyrol - Paone, Nadia (Proceedings e report, 2023)
Background: A growing body of scientific literature points to the consequences of various factors related to housing status on the well-being of individuals, particularly the elderly. This project aims to develop models that guarantee high-quality care for older people living in the province of Bolzano based on quantitative data analysis. Current changes within the family structure make it increasingly necessary to find new answers to the needs of the elderly. Based on these assumptions, we will investigate which support options encourage older people to live longer in their own homes. Methods: The sample is characterized by individuals residing in South Tyrol, living in their own homes and over 60 years of age. A 14-page questionnaire was administered in 2020 in German and Italian to 536 individuals. Utilizing a latent class model, we first tried to identify which factors act as resources and which as barriers for older people. In addition, using a quantile model, we investigated some aspects of satisfaction with the neighbourhood, measured with a 10-point scale. Results: The study shows that architectural barriers and harmful sanitary conditions are negatively associated with housing satisfaction. At the same time, social activities, a good relationship with the neighbourhood and safe living conditions act as resources. The role of neighbours and voluntary work increase housing satisfaction and ensure that older people stay in their homes as long as possible, playing a crucial role in this respect. With regards to the satisfaction with the neighbourhood, we can observe that the effect tends to be much stronger and more negative for individuals with an overall low neighbourhood frequency. Discussion: as in previous research, the objective indicators showed a more significant impact, while the positive results regarding some subjective factors deserve further investigation.